Analisis Nilai Moral dalam Cerita Rakyat Sultan Hadlirin dan Masjid At-Taqwa Loram Kulon Kudus - Fitmaya Intan Nazwa; Lu’luul Maknun; Muhammad Zaki Ali; Mohammad Kanzunnudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Folklore is an oral cultural heritage that contains moral values and local wisdom that are important to be transmitted to the younger generation. This study aims to identify and describe the moral values in the folklore